Sexual Excitement : Dynamics of Erotic Life. - Stoller, Robert (Maresfield library., 1986)
This is a study of sexual excitement. It is the fifth book on masculinity and femininity (gender identity), carrying forward ideas examined in Perversion: The Erotic Form of Hatred.